2014
DOI: 10.1016/j.jocn.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of delayed seizures, delayed cerebral ischemia and poor outcome with the use of levetiracetam versus phenytoin after aneurysmal subarachnoid hemorrhage

Abstract: Current guidelines recommend against the use of phenytoin following aneurysmal subarachnoid hemorrhage (aSAH) but consider other anticonvulsants, such as levetiracetam, acceptable. Our objective was to evaluate the risk of poor functional outcomes, delayed cerebral ischemia (DCI) and delayed seizures in aSAH patients treated with levetiracetam versus phenytoin. Medical records of patients with aSAH admitted between 2005-2012 receiving anticonvulsant prophylaxis with phenytoin or levetiracetam for >72 hours wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…In our study population, 42.7% patients had DCI, similar to previously reported rates (Karamchandani et al 2014). First, there is no significant difference between DCI and non-DCI groups in the time after SAH before EEG monitoring began (1.7±1.1 vs 1.7±1.2 days), or in the total duration of EEG monitoring (6.9±2.9 vs. 7.0±3.0) as measured by the two-sample KS test (p =0.001).…”
Section: Resultssupporting
confidence: 92%
“…In our study population, 42.7% patients had DCI, similar to previously reported rates (Karamchandani et al 2014). First, there is no significant difference between DCI and non-DCI groups in the time after SAH before EEG monitoring began (1.7±1.1 vs 1.7±1.2 days), or in the total duration of EEG monitoring (6.9±2.9 vs. 7.0±3.0) as measured by the two-sample KS test (p =0.001).…”
Section: Resultssupporting
confidence: 92%
“…18,19 However, Karamchandani et al found no significant difference in DIND between PHT vs. LEV treatment. 17 Surprisingly, adjusted analysis of our sample suggests LEV may actually be associated with the greatest risk of DIND- twice that of not receiving prophylactic AEDs. Although post hoc findings require cautious interpretation, they are nonetheless important given that current AHA/Stroke Guidelines state that the use of anticonvulsants is reasonable, without specifically recommending a particular anticonvulsant.…”
Section: Discussionmentioning
confidence: 66%
“…5,6,17–20 Rosengart et al analyzed 4 independent SAH trials and found patients who had received AEDs were 1.6 times more likely to have a poor outcome at 3 months, as well as being at increased risk for radiographic vasospasm, neurological deterioration, cerebral infarction, and elevated temperature during hospitalization. 5 Phenytoin, the first-line prophylactic AED traditionally used in SAH, has been shown to not only have a variety of adverse effects, but has also been correlated with poor neurologic recovery following SAH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, late seizures have been defined as occurring between 24 hours and 6 weeks of the initial hemorrhage, 13 more than 1 week following surgery for an SAH, 7 12 or more hours after hemorrhage but before surgical repair, 10 more than 14 days after the initial hemorrhage, 11,17 or as any seizures occurring after discharge. Alternatively, some have classified seizures in temporal relation to surgical repair, to the patient's hospital admission, or to initiation of AED therapy, 7,14,15,[18][19][20][21] whereas others have simply reported an overall incidence of any seizures that occurred during the patient's hospital stay. 9,[22][23][24][25][26][27][28] Furthermore, the definition of what constitutes a seizure was inconsistent among studies.…”
Section: Incidence and Impact Of Seizures Following Sahmentioning
confidence: 99%
“…The overall reported rate of postadmission seizures in SAH have ranged from 0 to 31%. 7,[9][10][11]14,15,17,20,[24][25][26]28,29,[33][34][35][36][37] The highest reported rate (31%) was observed by Dennis et al 29 in patients with nonconvulsive seizures detected by electroencephalogram (EEG). On the other hand, the study that did not report any seizures excluded patients with onset seizures and included only patients with SAH Hunt-Hess grades of I to III.…”
Section: Post-admission Seizuresmentioning
confidence: 99%